Luminescent converter of solar light into electrical energy. Review - Kulish, M.R.; Kostylyov, V.P.; Sachenko, A.V.; Sokolovskyi, I.O.; Khomenko, D.V.; Shkrebtii, A.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2016)
We review a status of the research on conversion of solar energy into electricity by using the systems that split the solar spectrum with a set of luminescent concentrators. Influence of the luminophore choice (rare-earth elements, dyes, or semiconductor quantum dots) and their characteristics as well as the luminescence quantum losses, when the light quanta travel inside the optical waveguide formed by the luminescent concentrator, were analyzed. The methods to minimize these losses, including optimal converter design, were discussed. The choice of design with stacked luminescent concentrators was demonstrated. The design of the stacked luminescent concentrators with optimized parameters of the transparent matrix and semiconductor quantum dots was investigated.